PHYCCTM Development Based On KKNI On Impuls And Momentum Material To Increase HOTS And Independent Character - Soeharto Soeharto (EDUCATIO: Journal of Education, 2017)
This study aimed to: (1) Produce KKNI-based PhyCCTM learning tool to improve HOTS and independent character Learners, (2) to know the result of HOTS improvement in Physics learning by using KKNI-based PhyCCTM Learning Tool developed, (3) to know the level of character category self-supporting Learners in Physics learning using KKNI-based PhyCCTM learning tools developed, and (4) to know the effect of applying learning using KKNI-based PhyCCTM learning device to control class and experiment on HOTS and Independent character of Learners. The developed product uses R & D method in the form of KKNI-based PhyCCTM learning device on impulse and momentum materials covering Syllabus, RPP, Teaching Material, LKPD, HOTS Evaluation Test and Self Character Sheet. The study was conducted in SMAN 8 Yogyakarta and SMAN 1 Kasihan. The results showed that (1) PhyCCTM-based learning tools KKNI worthy of the category "Good and Very Good". (2) KKNI-based PhyCCTM learning tools can improve HOTS for learners (Sig. 2-tailed by 0.001). (3) KKNI-based PhyCCTM learning tools can enhance the independent character of learners with the category "Fair". (4) KKNI-based PhyCCTM-developed learning tools effectively improve HOTS and independent character of learners (Sig. 0.000).